The Relationship Between the Implementation of Company System Digitalisation and Work Discipline as Determinants of Employee Performance: A Study of the Retail Industry in Cibitung - Umban Adi Jaya; Fauzan Manafi Albar; Indarta Priyana; La Ode Mbunai; Galih Raspati (Transpublika Publisher, 2025)
The development of digital technology has prompted companies to adopt digital systems in order to enhance operational efficiency and employee performance. However, adaptation to digitalization does not always have a direct impact on productivity, especially in the context of the retail industry which demands high discipline and adherence to work procedures. This study aims to analyze the influence of company system digitalization and work discipline on employee performance, as well as to evaluate the role of work discipline as a mediating variable in the context of the retail industry in Cibitung. This study uses a quantitative approach with path analysis method. Data were collected through online questionnaires distributed to 100 employees selected using purposive sampling. The results of the analysis indicate that the digitalization of company systems does not directly impact employee performance in a significant way. However, digitalization does have a beneficial and significant effect on work discipline, which in turn has a positive and significant impact on employee performance. Although the role of work discipline as a mediator in the link between digitalization and performance may not be statistically significant, there are still signs of partial mediation. Based on these results, it can be concluded that just introducing digital technology is not sufficient; there needs to be additional focus on improving work discipline to fully optimize the effect on employee productivity. This research offers practical advice for retail managers, emphasizing the need to combine digital policies with discipline-strengthening tactics such as training, monitoring, and incentives to enhance performance.